SISTEM INFORMASI PEMERINGKATAN PRESTASI SISWA BERBASIS WEB PADA SMK PELITA PESAWARAN - Muhammad Najib Dwi Satria (Universitas Teknokrat Indonesia, 2022)
Pelita Pesawaran Vocational School is a university that has a myriad of achievements by students, both academic and non-academic. In reporting every year there is an increase in terms of the number of achievements that have been achieved, so that some adjustments to conditions are needed. Student achievements that have been achieved should actually be archived into a system that can be processed in order to obtain accurate and relevant results. Therefore we need a system that can process achievement data accurately and integrated and can display the ranking of student achievement at the level of study programs, faculties and university levels. With the creation of a system entitled Web-Based Student Achievement Rating System at Pelita Pesawaran Vocational School, it is hoped that it will be able to help Pelita Pesawaran Vocational School in processing achievement data every year and be able to rank student achievement so that Pelita Pesawaran Vocational School can obtain accurate and relevant information on outstanding students in accordance with the data provided. there is. The Web-Based Student Achievement Ranking System at Pelita Pesawaran Vocational School is designed using PHP, CSS, JavaScript, and HTML programming languages which are used as interfaces while for data storage media using MySql.languages which are used as interfaces while for data storage media using MySql.